Answer :

A ^{– 1} = B =

|B| = 1(3 – 0) – 2( – 1 – 0) – 2(2 – 0)

= 3 + 2 – 4

|B| = 1

Now, B ^{– 1} =

Cofactors of B are:

C_{11} = – 3 C_{21} = 2 C_{31} = 6

C_{12} = 1 C_{22} = 1 C_{32} = 2

C_{13} = 2 C_{23} = 2 C_{33} = 5

adj B =

=

So, adj B =

Now, B ^{– 1} =

(AB) ^{– 1 =} B ^{– 1} A ^{– 1}

=

Hence, =

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

RELATED QUESTIONS :

Using matrices, solve the following system of equations:

2x + 3y + 3z = 5, x – 2y + z = – 4, 3x – y – 2z = 3

Mathematics - Board PapersIf find Using solve the system of equation

Mathematics - Board PapersSolve for using properties of determinants.

**OR**

Using elementary row operations find the inverse of a matrix and hence solve the following system of equations

Mathematics - Board Papers